The double dangerous book for boys - Iggulden, Conn; Iggulden, Cameron (HarperCollins Publishers, 2019)
"From the #1 New York Times bestselling author of The Dangerous Book for Boys comes the long-awaited sequel - another action-packed adventure guide featuring full-color illustrations, perfect for dads, grads, and boys of all ages.The Double Dangerous Book for Boys is a treasure trove of the essential activities and skills that have defined generations of boyhoods, from building a treehouse to fishing to finding true north."--Amazon.